Quantifying the Effects of Historical Land Cover Conversion Uncertainty on Global Carbon and Climate Estimates. Issue 2 (23rd January 2018) - Di Vittorio, A. V.; Mao, J.; Shi, X.; Chini, L.; Hurtt, G.; Collins, W. D.
Abstract: Previous studies have examined land use change as a driver of global change, but the translation of land use change into land cover conversion has been largely unconstrained. Here we quantify the effects of land cover conversion uncertainty on the global carbon and climate system using the integrated Earth System Model. Our experiments use identical land use change data and vary land cover conversions to quantify associated uncertainty in carbon and climate estimates. Land cover conversion uncertainty is large, constitutes a 5 ppmv range in estimated atmospheric CO2 in 2004, and generates carbon uncertainty that is equivalent to 80% of the net effects of CO2 and climate and 124% of the effects of nitrogen deposition during 1850–2004. Additionally, land cover uncertainty generates differences in local surface temperature of over 1°C. We conclude that future studies addressing land use, carbon, and climate need to constrain and reduce land cover conversion uncertainties. Plain Language Summary: In order to help people adjust to and lessen the local impacts of global change, international modeling efforts aim to understand global change and its impacts on humans and the environment. Most human activities are on land, such as living, agriculture, and wood harvest, and these activities both contribute to and are affected by global change. Modeling how these activities change vegetation cover, and subsequently the greater environment, is difficult and highly uncertain, yet crucial to understanding impacts of global change. Here we estimate an uncertainty in year 2004 global forest cover of 5.1 km 2 using one historical agriculture pattern, and corresponding uncertainties of 5 ppmv in atmospheric carbon dioxide concentration and greater than 1°C in local surface temperature. The associated uncertainty in land carbon storage is 80% of the estimated additional carbon stored due to historical changes in carbon dioxide concentration and climate, and 124% of the additional carbon attributed to nitrogen deposition. We conclude that future studies of global change and its impacts on humans and the environment need to constrain and reduce land cover uncertainties. Key Points: Land cover conversion uncertainty constitutes a 5 ppmv range in estimated atmospheric CO2 concentrations in 2004 Land cover conversion uncertainty generates land carbon uncertainty that is 80% of net CO2 and climate effects on terrestrial carbon stock through 2004 Land cover conversion uncertainty generates a range in projected local surface temperature of over 1°C (1984‐2004 average)